2013
DOI: 10.1128/aac.02237-12
|View full text |Cite
|
Sign up to set email alerts
|

Rattusin, an Intestinal α-Defensin-Related Peptide in Rats with a Unique Cysteine Spacing Pattern and Salt-Insensitive Antibacterial Activities

Abstract: c Cationic antimicrobial peptides are essential components of the innate immune system. As a major family of mammalian antimicrobial peptides, defensins are expressed mainly by mucosal epithelial cells and promyelocytes. Despite the capacity to kill a broad spectrum of bacteria through physical disruption of membranes, most defensins show substantially reduced antibacterial activities in the presence of monovalent and divalent cations, thereby limiting their therapeutic potential, particularly for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 53 publications
1
17
1
Order By: Relevance
“…In a previous study, Patil et al . also found that synthetic RTSN refolded into a dimeric form that showed efficient antibacterial activity31 similar to the characteristics of r -RTSN observed in this study. They also proposed that RTSN forms a homodimer and/or oligomer through intra- and/or intermolecular SS bonds, and that the SS bond pairings may be random.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In a previous study, Patil et al . also found that synthetic RTSN refolded into a dimeric form that showed efficient antibacterial activity31 similar to the characteristics of r -RTSN observed in this study. They also proposed that RTSN forms a homodimer and/or oligomer through intra- and/or intermolecular SS bonds, and that the SS bond pairings may be random.…”
Section: Discussionsupporting
confidence: 86%
“…The determined MIC was 8 μM, which is slightly greater than previously reported data (~4 μM against E. coli O157:H7)31. This small difference may result from differences in the bacterial species and/or experimental conditions.…”
Section: Resultscontrasting
confidence: 59%
See 3 more Smart Citations